The Effect of Education Background Teacher on The Learning Process In Class At Muhammadiyah First Middle School Ambon - Rehalat, Aminah; Nurul 'ainy, Zuhria (Perspektif Pendidikan dan Keguruan, 2022)
The purpose of this study was to determine the educational background of teachers on the learning process in the classroom at Muhammadiyah Ambon Junior High School. The method used in this study is a quasi-experimental or quasi-experimental method where the researcher uses an experimental class and a control class for comparison. The results found are, based on the results of research and data analysis that has been carried out, it can be concluded that there is an influence of teacher educational background on the learning process in the classroom at Muhammadiyah Ambon Junior High School experimental studies on economic subjects. This can be seen from the comparison data of the results of the pre-test and post-test experimental class students who took part in the study with teachers who had taken a bachelor's degree. Based on these results, it can be concluded that there is an increase in student learning outcomes in economics.